2016
DOI: 10.1111/ajt.13766
|View full text |Cite
|
Sign up to set email alerts
|

On Patients Who Purchase Organ Transplants Abroad

Abstract: The international transplant community portrays organ trade as a growing and serious crime involving large numbers of traveling patients who purchase organs. We present a systematic review about the published number of patients who purchased organs. With this information, we discuss whether the scientific literature reflects a substantial practice of organ purchase. Between 2000 and 2015, 86 studies were published. Seventy-six of these presented patients who traveled and 42 stated that the transplants were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 94 publications
0
24
0
Order By: Relevance
“…Special emphasis should be given to family systems and dynamics, and assessment for the presence of coercion, undue pressure, or financial motivation . Socioeconomic stability should be assessed, including review of donor candidate's lifestyle and occupation, and confirmation of gainful employment and/or financial support from family.…”
Section: Comprehensive Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Special emphasis should be given to family systems and dynamics, and assessment for the presence of coercion, undue pressure, or financial motivation . Socioeconomic stability should be assessed, including review of donor candidate's lifestyle and occupation, and confirmation of gainful employment and/or financial support from family.…”
Section: Comprehensive Evaluationmentioning
confidence: 99%
“…Generally, international donors are family members or friends of patients with ESKD who visit the United States to serve as living kidney donors. Whereas some countries prohibit international donors due to concerns for organ trafficking or transplant commercialism, the United States has no such prohibition . A recent study of US Organ Procurement and Transplantation Network (OPTN) registry data found that international living kidney donors were tightly clustered among a small number of transplant centers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ambagtsheer et al (1) noted that South Korea is one of the two "most commonly reported departure countries" for TT, and this may create the false impression that South Korea is a major source of transplant tourists. The paper demonstrates the problems with drawing conclusions about TT activities from reviews of the peerreviewed literature.…”
Section: To the Editormentioning
confidence: 99%
“…Second, the increased availability of data concerning TT from particular countries may simply reflect efforts taken in those countries to address the problem of TT through research and reporting. The Korean data reported by Ambagtsheer et al (1), for example, included a large number of liver transplantation (LT) cases, whereas the data from most other countries included only KT cases. In comparison with KT, reports of LT abroad in the primary literature are scarce, perhaps reflecting the common perception that TT is largely a concern of persons working in the field of KT.…”
Section: To the Editormentioning
confidence: 99%